2017
DOI: 10.1101/183269
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation of RT-qPCR approaches to monitorPseudomonas syringaegene expression during infection and exposure to pattern-triggered immunity

Abstract: Pseudomonas syringae pv. tomato DC3000 (DC3000) is an important model plant pathogen, with a fully annotated genome and multiple compatible plant hosts. Very few studies have examined the regulation of DC3000 gene expression in vivo. We developed a RT-qPCR assay to monitor transcriptional changes in DC3000 inoculated into Arabidopsis thaliana leaves during disease and exposure to pattern-triggered immunity (PTI). In our approach, bacterial RNA concentrations in total tissue RNA are standardized using P.syringa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…For example, the expression of rpoD at 6 hours post-inoculation was almost 200 times greater than in the inoculum, and 6 times greater than the expression at 168 hours. rpoD has been used in the past as a qPCR reference gene (Smith et al 2018); however, its expression, at least under certain conditions, is too variable for this purpose, as observed in our experiments. ftsZ showed the same trend of early increased expression and subsequent decrease in planta; however, the relative expression in the inoculum was more variable (Figure 7A and Supplementary Figure S8B).…”
Section: Bacterial Gene Expression Of Select Biological Processes During Long-term Adaptation Of a Non-pathogen Inside Plantsmentioning
confidence: 79%
See 1 more Smart Citation
“…For example, the expression of rpoD at 6 hours post-inoculation was almost 200 times greater than in the inoculum, and 6 times greater than the expression at 168 hours. rpoD has been used in the past as a qPCR reference gene (Smith et al 2018); however, its expression, at least under certain conditions, is too variable for this purpose, as observed in our experiments. ftsZ showed the same trend of early increased expression and subsequent decrease in planta; however, the relative expression in the inoculum was more variable (Figure 7A and Supplementary Figure S8B).…”
Section: Bacterial Gene Expression Of Select Biological Processes During Long-term Adaptation Of a Non-pathogen Inside Plantsmentioning
confidence: 79%
“…For example, the expression of rpoD at 6 hours post-inoculation was almost 200 times greater than in the inoculum, and 6 times greater than the expression at 168 hours. rpoD has been used in the past as a qPCR reference gene (Smith et al . 2018); however, its expression, at least under certain conditions, is too variable for this purpose, as observed in our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…RT-qPCR data were normalized to recA (PSPTO_4033) and rpoD (PSPTO_0537) used as reference genes. The stability of recA and rpoD expression in planta at 24 and 48 h after inoculation was confirmed as described by Smith et al (36), using a synthetic double-stranded DNA gBlock (Integrated DNA Technologies, Coralville, IA, USA) and PtoDC3000-specific 16S rRNA primers.…”
Section: Monitoring Bacterial Gene Expression In Plantamentioning
confidence: 99%
“…We assessed the stability of expression of several house-keeping genes in order to choose those suitable for use as reference genes for normalization of gene expression (36) and found that recA and rpoD were expressed at very similar levels at 24 and 48 hours after inoculation.…”
Section: Auxin Modulates Bacterial Virulence-related Gene Expression mentioning
confidence: 99%
See 1 more Smart Citation